2020
DOI: 10.1002/ece3.6540
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the endangered European weather loach (Misgurnus fossilis) via water and sediment samples: Testing multiple eDNA workflows

Abstract: The European weather loach ( Misgurnus fossilis ) is classified as highly endangered in several countries of Central Europe. Populations of M. fossilis are predominantly found in ditches with low water levels and thick sludge layers and are thus hard to detect using conventional fishing methods. Therefore, environmental DNA (eDNA) monitoring appears particularly relevant for this species. In previous studies, M. fossilis was surveyed followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Furthermore, the widely used saturated phosphate buffer method for extracting only extracellular DNA (Taberlet et al, 2012) was the worst performing extraction method, resulting in low recovery of artificially spiked DNA compared to other methods tested in this study. Poor extraction efficiency using a phosphate buffer has been highlighted previously by Kusanke et al (2020), who found that its use resulted in significantly lower DNA yields of the European loach ( Misgurnus fossilis ) in sediment. A case study on historical lake sediments found that phosphate buffer extractions were consistently outperformed by the unmodified PowerSoil kit protocol when assessing sedDNA yields of various terrestrial animals including arthropods, eukaryotes and vertebrates (Capo et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the widely used saturated phosphate buffer method for extracting only extracellular DNA (Taberlet et al, 2012) was the worst performing extraction method, resulting in low recovery of artificially spiked DNA compared to other methods tested in this study. Poor extraction efficiency using a phosphate buffer has been highlighted previously by Kusanke et al (2020), who found that its use resulted in significantly lower DNA yields of the European loach ( Misgurnus fossilis ) in sediment. A case study on historical lake sediments found that phosphate buffer extractions were consistently outperformed by the unmodified PowerSoil kit protocol when assessing sedDNA yields of various terrestrial animals including arthropods, eukaryotes and vertebrates (Capo et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…Some previous studies have used similar sediment masses (3–10 g) to target fish DNA in both contemporary and historical sediments, although their rationale for choosing sediment mass in this range was not specifically discussed (Kuwae et al, 2020; Ogata et al, 2021; Sakata et al, 2020a, 2020b; Sales et al, 2019, 2021; Turner et al, 2015; Valdez‐Moreno et al, 2019). By contrast, other studies have used smaller amounts of sediment (<0.5 g) and successfully detected fish with either targeted or community approaches, also in a range of contemporary and historical sediments (Baldigo et al, 2017; Eichmiller et al, 2014; Kusanke et al, 2020; Matisoo‐Smith et al, 2008; Nelson‐Chorney et al, 2019; Olajos et al, 2018; Shaw et al, 2016; Stager et al, 2015). The reasons for the successful detection of fish sedDNA in smaller sediment masses remain unclear, yet there may be other factors (such as those discussed below) that influence the ability to extract and detect fish sedDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling from the field is the experimental step most at risk of cross-contamination. According to previous studies, 10% bleach can be used to clean sampling appliances, including the ship or boat used, and mouth masks and disposable latex gloves should be worn by samplers to prevent DNA contamination (Sigsgaard et al, 2017;Muha et al, 2019;Kusanke et al, 2020;Riaz et al, 2020). Unmanned aerial vehicles (UAVs) have been used as a new technique to collect environmental samples for eDNA studies and avoid contamination (Doi et al, 2017).…”
Section: Contaminationmentioning
confidence: 99%
“…In all of the cases mentioned, eDNA-based identification outperformed traditional detection, revealing targeted species' presence even at low eDNA molecule concentrations. Further development and validation of eDNA protocols has been conducted in recent years to further enhance the detection reliability of endangered taxa, additionally aiming to also provide information on quantities and abundances (Thomsen et al 2012;Harper et al 2018;Kusanke et al 2020). The further development of eDNA methodology has led to the implementation of eDNA-based biomonitoring of endangered taxa in standard national legislation, similarly to routine monitoring of great crested newts in the United Kingdom.…”
Section: Monitoring Species Of Interestmentioning
confidence: 99%